Spatiotemporal impact of mesoscale eddies on chlorophyll-a concentration in the North Atlantic - Cai, Jinghui; Sun, Jialong; Qin, Siyuan; Li, Yaonan (Frontiers in Marine Science, 2025)
IntroductionMesoscale eddies play a crucial role in energy transport and ecological regulation in the North Atlantic Ocean.MethodsBased on multi-source datasets, including satellite remote sensing and Argo float observations from 2009 to 2018, this study employs the Velocity Gradient Detection (VGD) method to identify eddy boundaries and cores, in combination with a spatiotemporal dynamic matching technique, to systematically analyze eddy characteristics and their impacts on chlorophyll-a (Chl-a) concentrations.ResultsResults show that eddy activity is predominantly concentrated in the Gulf Stream extension region (24°N–48°N, 40°W–60°W). Cyclonic eddies significantly elevate surface Chl-a concentrations (0.6–1.8 mg/m³) through upwelling processes, while anticyclonic eddies induce localized enrichment (15%–25% increase) along their peripheries, exhibiting marked seasonal variability. Vertical analysis reveals that eddy-induced Chl-a anomalies can peak at depths of 50–70 m, effectively enhancing subsurface primary productivity. Overall, eddy-driven Chl-a variations contribute approximately 20% to regional primary production.DiscussionThese findings highlight the functional importance of mesoscale eddies in regulating phytoplankton biomass and underscore their role in advancing our understanding of the marine carbon cycle under changing climate conditions.